Factor 26r3s + 52r5 – 39r2s4. What is the resulting expression? 13(2r3s + 4r5 – 3r2s4)
13r2s(2r + 4r3 – 3s3)
13r2(2rs + 4r3 – 3s4)
13r2(26r3s + 52r5 – 39r2s4)

Answers

Answer 1
Answer:

Answer:

Option 3rd is correct

13r^2(2rs+4r^3-3s^4)

Step-by-step explanation:

GCF (Greatest common factor) is the largest number that divides the two number.

Factor 26r^3s+52r^5-39r^2s^4

Find the GCF of the given expression.

GCF of 26r^3s, 52r^5 and 39r^2s^4 is, 13r^2

then;

13r^2(2rs+4r^3-3s^4)

Therefore, the  resulting expression is, 13r^2(2rs+4r^3-3s^4)

Answer 2
Answer:

Answer:

The Given Expression is

26r^3s + 52r^5 -39r^2s^4\n13* 2* r* r^2 * s + 13* 2* 2* r^2* r^2* r- 13 * 3* r^2* s * s^3\n\n\text{Taking out common factors}\n\n13r^2(2 rs + 2* 2 r^3 -3 s^4)\n\n13r^2(2 r s+ 4 r^3 - 3 s^4)

Option  <strong>13r^2(2 rs + 4 r^3 - 3 s^4) is correct option.


Related Questions

A square can be changed into a rectangle by increasing the width by 3 units. Which expression represents the area of the rectangle in square units? (A) x^2+8x+15 (B) x2+15 (C) 2x +8 (D) 2x+15
Which of the following is a necessary reactant for cellular respiration to occur?Carbon dioxide Nitrogen Oxygen Water
the population of mastertown was 23,000 in 2012. assume that mastertowns population increases at a rate of 2% per year. write an equation to model the population of mastertown (y) based on numbers of years since 2012 (x)
Please help I don’t know
If 120% is 360,what is 100%

You want to place a towel bar that is 10 1/4 inches long in the center of a door that is 26 1/3 inches wide. How far should you place the bar from each edge of the door

Answers

If the bar is in the center of the door then we know that there is the same amount of space on each side of the bar. Call this space 's'. This is what we need to find. We also know the total width of the door and the total length of the bar. With this info we can set up and equation to represent the relationship:

s=(26(1)/(3) - 10(1)/(4))/(2)

and then solve for s. This is easer to do if we convert the two fractions to a common base and rearrange the equation so that instead of dividing by 2, we instead multiply by 1/2:

s=26(4)/(12) - 10(3)/(12) * (1)/(2) = 13(1)/(12) * (1)/(2) = (193)/(12) * (1)/(2) = (193)/(24) = 8 (1)/(24)inch 

What is :

(49^x)(7^x^2)=2401^2

Answers

(49^x)(7 ^(x^2))=2401^2 \n \n( (7^2)^x)(7 ^(x^2))= (7^4) ^2 \n \n 7 ^(2x)\cdot 7^(x^2)=7^(8) \n \n 7 ^(2x+x^2) =7^(8) \n \n2x+x^2 =8

 x^2-2x-8 = 0\n \n a=1, \ b=-2, \ c=-8 \n \n\Delta =b^2-4ac = (-2)^2 -4\cdot1\cdot (-8) = 4 +32 =36 \n \nx_(1)=(-b-√(\Delta) )/(2a)=(2-√(36))/(2 )=( 2-6)/(2)=(-4)/(2)=-2 \n \nx_(2)=(-b+√(\Delta) )/(2a)=(2+√(36))/(2 )=( 2+6)/(2)=(8)/(2)= 4 \n \nAnswer: \ x=-2 \ \ or \ \ x=4

(49^x)(7^(x^2))=2401^2\n \n7^(2x) \cdot7^(x^2)=(7^4)^2\n \n7^(2x+x^2)=7^8\ \ \ \Leftrightarrow\ \ \ 2x+x^2=8\ \ \ \Leftrightarrow\ \ \ x^2+2x-8=0\n \nx^2-2x+4x-8=0\ \ \ \Leftrightarrow\ \ \ x(x-2)+4(x-2)=0\n \n(x-2)(x+4)=0\ \ \ \Leftrightarrow\ \ \ ( x-2=0\ \ \ \vee\ \ \ x+4=0)\n.\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ x=2\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ x=-4

Write the equation of the line, in slope-intercept form, with thefollowing information:
1
slope:
2
y-intercept: (0, 2)


Please help fast

50 points

Answers

Answer:

The answer to the question provided is y=1/2x+2

Subtract 3 from 4/9 of 20

Answers

Answer:

5 8/9

Step-by-step explanation:

20*4/9=8 8/9

8 8/9–3=5 8/9

What is
3x10 squared 5 + 2x10 squared 5 + 4x10 squared 5

Answers

Answer:

900000

Step-by-step explanation:

3*10^5+2*10^5+4*10^5

we can start by adding the base numbers (3, 2 & 4) since they are all being multiplied by 10^5: 3+2+4=9

so then we have 9*10^5

then we solve for 10^5, which is 10*10*10*10*10 or 100000

so we then have 9*100000 and we get

900000

Answer:

9x^10 + 15

Step-by-step explanation:

Select the correct difference. -3z 7 - (-5z 7) 2z7 8z14 -2z7 2z

Answers

Answer:

2z^(7)).

Step-by-step explanation:

Given  : -3 z^(7) - ( -5 z^(7))

To find : Select the correct difference.

Solution : we have given

-3 z^(7) - ( -5 z^(7)).

Open the parenthesis

-3 z^(7) + 5 z^(7)).

By the rule ( + - = -)  .

2z^(7)).

Therefore,  2z^(7)).

-3z^7 - (-5z^7) = -3z^7 + 5z^7 = 2z^7